2008
DOI: 10.1007/s00395-008-0748-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mutational hot spots in LMNA encoding lamin A/C in patients with familial dilated cardiomyopathy

Abstract: The familial form of dilated cardiomyopathy (DCM) occurs in about 20%-50% of DCM cases. It is a heterogeneous genetic disease: mutations in more than 20 different genes have been shown to cause familial DCM. LMNA, encoding the nuclear membrane protein lamin A/C, is one of the most important disease gene for that disease. Therefore, we analyzed the LMNA gene in a large cohort of 73 patients with familial DCM. Clinical examination (ECG, echocardiography, and catheterization) was followed by genetic characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 38 publications
1
60
0
Order By: Relevance
“…All affected family members were shown to have the variant LMNA:c.656A4C, which has been previously demonstrated in an unrelated 43-year-old man with DCM. 17 In addition, the four most severely affected family members were found to have a previously not described variant in the gene for titin, TTN:c.14563C4T (p L4855F). Doubly heterozygous family members showed a substantially more severe clinical course, with respect to age of terminal CHF and heart transplantation, and a number of cardiological and histological LMNA/TTN mutations in severe DCMparameters (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…All affected family members were shown to have the variant LMNA:c.656A4C, which has been previously demonstrated in an unrelated 43-year-old man with DCM. 17 In addition, the four most severely affected family members were found to have a previously not described variant in the gene for titin, TTN:c.14563C4T (p L4855F). Doubly heterozygous family members showed a substantially more severe clinical course, with respect to age of terminal CHF and heart transplantation, and a number of cardiological and histological LMNA/TTN mutations in severe DCMparameters (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 97%
“…individual with DCM, 17 and a previously unreported variant was found in the gene for titin (TTN:c.14563C4T; p.L4855F). There were no other variants in genes associated with cardiological phenotypes.…”
Section: Targeted Wesmentioning
confidence: 99%
“…Moreover, this apoptotic effect could be attenuated by pharmacological blockade of the MEK1/ERK1/2 pathway. Study of gene expression profile showed that mouse models of laminopathies also displayed ERK pathway activation in heart muscle [43,44]. Importantly, the pharmacological blockade of the ERK1/2 pathway prevented the development of DCM in this model [45].…”
Section: Introductionmentioning
confidence: 84%
“…Interestingly, both non-conserved residues are mutated to a proline and located adjacent to pathogenic residues. These are p.R190, associated with DCM when mutated to Trp or Gln (Perrot, et al, 2009;Sylvius, et al, 2005), and p.Y267, associated with EDMD and DCM when mutated to His or Cys (Carboni, et al, 2008;Vytopil, et al, 2003). Proline is not found in the centre of a straight alpha-helix, due to its helix breaking attributes (Richardson and Richardson, 1988).…”
Section: Discussionmentioning
confidence: 99%